Is it coping or is it a vice? Understanding stereotypic behaviors in horses - Carissa Wickens; Camie Heleski (EDIS, 2024)
This article will share what science has revealed about stereotypic behaviors, and how this information can be applied to better manage and thus improve the welfare of horses with stereotypic behavior. Written by Carissa Wickens and Camie Heleski, and published by the Veterinary Medicine—Department of Large Animal Clinical Sciences, UF/IFAS Extension, January 2024.